Multi-objective resource allocation in interference-limited M2M communication networks. (2016) - Hussain, Fatima; Anpalagan, Alagan; Naeem, Muhammad; Khwaja, Ahmed Shaharyar
In this paper, we propose a multi-objective optimisation-based solution to the problem of resource allocation in interference-limited machine to machine (M2M) communication. We consider machine type communication devices (MTCDs) in a clustered network structure, where they are divided into clusters and the devices belonging to a cluster communicate to cluster head (or controller). The cluster head aggregates the traffic and relays from MTCDs to eNB and vice versa. We maximise the number of admitted MTCD controllers and throughput with least interference caused to conventional primary users. We formulate the problem as a mixed-integer nonlinear problem with multiple objectives and apply meshed adaptive direct search (MADS) algorithm which gives guaranteed convergence. Simulation results show the effects of varying different parameters on cumulative throughput and the number of admitted MTCD controllers.